Clinical-imagistic aspects of supernumerary teeth - Mioara Decusară; Cerasella Dorina Şincar; Gina Păuniţa Grecu; Gabriela Popa; Gabriel Valeriu Popa (Amaltea Medical Publishing House, 2019)
Supernumerary teeth represent isolated dental abnormalities by dental excess occurring when the disruptive factor acts in the stage of dental formation (induction and proliferation). It may be the result of the intervention of some hereditary, phylogenetic, local factors (disturbing factors in the dental proliferation stage), but may appear as clinical manifestations in genetic syndromes (cleido-cranial dysplasia and Gardner's syndrome). It determines aesthetic, occlusal, periodontal, clinical and functional changes, the diagnosis of certainty being given by radiological investigations. Since supernumerary teeth do not affect the quality of the alveolar bone, the prognosis is favorable, and surgical (extraction) and orthodontic treatment restores the normal aesthetic and functional aspect of the dental-maxillar apparatus.